Preserving the Past for the Future: The Importance of Archival Information in Forestry. - Roger Mills (Issues in Science and Technology Librarianship, 2006)
Trees include some of the longest-lived organisms on Earth and gathering comprehensive data about them may take decades or even centuries. The long-standing problems of identifying, preserving and making accessible printed or hand-written information, which will be of use to future generations, have now been joined by new challenges in the handling of electronic and multimedia sources, in often short-lived formats and in overwhelming volume. This paper reviews some of the initiatives at local, national and international level, which are seeking to support sustainable forest management through sustainable management of information, illustrating with a case study of the century-old Oxford Forest Information Service. [ABSTRACT FROM AUTHOR]